Sinhogarismo, política social y género etnografías sobre situaciones y rutas habitacionales en Santiago Centro - Lara Martínez, Mauricio Javier (2022)
This research describes and analyzes the problem of homeless populations and in "housing emergency" in Santiago de Chile, giving an account of the structural and historical crisis of housing and the city, of the institutionality built and developed to address this phenomenon and on the ways of carrying it, negotiating and moving around of the people involved. A historical tour of the institutional development of social housing and social assistance policy is made, giving an account of how in an urban and political context of neoliberal transformation these have concentrated, isolated and marginalized poor populations. This has been done both in social housing neighborhoods and in hostels, maintaining these spaces with material precariousness, hyperdensification and abandonment, which has finally reproduced and deepened their exclusions. In this situation of exclusion, the ways in which people in "housing emergency" are described, based on their sex-gender identifications and male domination of spaces, seek to ensure a space to live. For this, two groups are analyzed from ethnographic approaches that were considered different ways of dealing with this situation, firstly a Solidarity Residence and secondly a Housing Committee of the Santiago Centro commune. It is complemented by a problematization of gender dynamics and conflicts in the same organizations that somehow threaten to maintain social order and sometimes the very possibility of organization and mobilization. Consequently, it is analyzed how groups and social movements of homeless populations counteract the real estate, institutional and masculine forces according to their situations in the sex-gender system.
Keywords: Geschichte 1973-2023; Sin hogar; género; rutas habitacionales; Sozialer Wohnungsbau; Sozialpolitik; Obdachlosigkeit; Santiago de Chile; Hochschulschrift